Application Of Wingeom-Assisted Think Pair Share Model to Students' Mathematical Communication Skills - hamidah; Wijaya kusuma, Jaka; Hindayati, Iin (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
The cooperative learning model of Think Pair Share assisted by WinGeom provides an opportunity for students to develop their mathematical communication skills during the learning process. This study aims to determine the effect of implementing the Think Pair Share cooperative learning model assisted by WinGeom on mathematical communication skills among junior high school students in Geometry. The research uses a quasi-experimental design with pretest-posttest 1, 2, and 3. The population of this study consists of grade VIII students at SMP Negeri 7 Serang City. The sample includes students from classes VIII-A and VIII-B class was selected randomly. Data collection techniques used mathematical communication skills tests. This study compares Think Pair Share assisted by WinGeom with conventional learning methods. ANOVA was used to analyze the effectiveness of the two learning methods. ANOVA test results for each posttest indicate that Think Pair Share assisted by WinGeom has a different effect compared to conventional learning. The study results show a significant difference between the average mathematical communication skills of students in the experimental class and the control class. This means that the cooperative learning model of Think Pair Share assisted by WinGeom has an impact on junior high school students' mathematical communication skills. In the future, this learning method could be a solution for teachers worldwide to improve students' learning achievements, particularly in mathematical communication skills. Keywords: Think pair share model, WinGeom, Mathematical Communication, Cooperative